2020
DOI: 10.2147/prbm.s231577
|View full text |Cite
|
Sign up to set email alerts
|

Spotlight on the Fear of Cancer Recurrence Inventory (FCRI)

Abstract: Fear of cancer recurrence (FCR) is a pervasive concern for people living with cancer. The rapidly expanding FCR literature has been weakened somewhat by use of miscellaneous FCR measures of varying quality. The Fear of Cancer Recurrence Inventory (FCRI) has been widely used in observational and intervention studies and the FCRI severity subscale, also known as the FCRI-Short Form (FCRI-SF), is often used to identify potential cases of clinically significant FCR. Given the FCRI’s increasing use in research and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 81 publications
2
59
4
2
Order By: Relevance
“…Most studies used the Fear of Cancer Recurrence Inventory (FCRI) 25,26,28,29,32,35 . The FCRI is a widely used 42‐item multi‐dimensional FCR measure with strong psychometric properties 36,37 . One study did not use a validated FCR measure 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Most studies used the Fear of Cancer Recurrence Inventory (FCRI) 25,26,28,29,32,35 . The FCRI is a widely used 42‐item multi‐dimensional FCR measure with strong psychometric properties 36,37 . One study did not use a validated FCR measure 30 .…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that people with higher levels of FCR at baseline reported the greatest decrease in FCR post-intervention; however, there is currently no consensus regarding what cut-off score constitutes “high” FCR, nor what score is indicative of referral for intervention. Brief measurement tools have shown promise and may reduce the cognitive burden on patients while quickly identifying those with greatest clinical need (Fardell et al, 2018 ; Rudy et al, 2020 ; Smith et al, 2020 ). Further research to identify a clinically-meaningful FCR cut-off score for people affected by melanoma will allow for pre-intervention screening and more precise targeting of treatments and interventions (Lebel et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Mirosevic et al article (Mirosevic et al, 2019) set their cut-off against the validated Fears of Cancer Recurrence Inventory (FCRI). A review of the FCRI has raised concerns about the low cut-off on this measure (Smith et al, 2020). Hence, careful attention needs to be paid to the actual wording and psychometric properties of the measures used.…”
Section: Discussionmentioning
confidence: 99%